INVESTIGATING THE DESCRIPTIVE WRITING MASTERY USING PASSIVE SENTENCES (A Case Study At Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi In English Department) - Miftahul Khairani, Fridiyanto (At-Tazakki: Jurnal Kajian Ilmu Pendidikan Islam dan Humaniora, 2020)
Abstract: the issue of English teaching is always an important one and it will continue to be one of the dominant points in education problems. Through qualitative method, this study aimed to explore the investigating about students’ mastery in descriptive writing specifically in using passive sentences. The data were collected by test, observation, and in-dept interview with English lecturer and English program in Islamic state university Sulthan Thaha Saifuddin Jambi. The results of the data analysis revealed that many students are not mastery in descriptive writing in using passive sentences. The findings show that passive sentences are not discussed specifically in the classrooms. Recommendation for English subject to make a lesson plan about passive sentences and practice them in a scientific writing.Keywords: Passive sentences, Descriptive writing, English teaching